A patient with psittacosis from a pigeon: A reminder of the importance of detailed interviews and relative bradycardia. (2021) - Fukui, Sayato; Kawamura, Wataru; Uehara, Yuki; Naito, Toshio
Abstract: A 43-year-old man was brought to our hospital with fever. The initial diagnosis was bacterial pneumonia, and ampicillin/sulbactam was administered. However, defervescence was not achieved, and relative bradycardia was observed. Detailed history-taking revealed that the patient had been involved in caring for a wild pigeon before hospitalization. We changed the antimicrobial therapy to minocycline and the patient' s condition improved. Chlamydophila psittaci antibody was subsequently found to be increased four-fold, and psittacosis was diagnosed. This case acts a reminder to clinicians of the importance of both the history of exposure to any birds and vital signs, including relative bradycardia.